Negative rumination in depression subtypes with melancholic features and anxious distress - Wang, Hong-li; Shi, Xiao-ning; Zhao, Jin-long; Jia, Qiong; Xu, Wei; Dun, Wen-wen; Zhao, Ying-ying (Frontiers in Psychology, 2025)
BackgroundAberrant cognition is one of the crucial symptoms of depression. However, whether the negative rumination participates in depression with melancholic features or anxious distress remains unclear.MethodsIn this study, we addressed this issue by compiling a questionnaire that can comprehensively measure the negative cognitive processing bias in depression. We also conducted an exhaustive analysis of its influencing factors, including the subtype of depression, age, gender, age of onset, family history of mental disorder, and education year.ResultsWe found that depression increased negative attention bias, negative memory bias, negative interpretation bias, and negative rumination bias. Importantly, among the several dimensions of negative cognitive bias, negative rumination bias was more serious in the melancholic than anxious subgroup. Furthermore, Spearman rank correlation analysis showed that negative rumination bias correlates with family history and age of onset of depression.LimitationsWe mainly explored melancholic and anxiety subgroups and did not include other subtypes. Due to time constraints, we did not conduct long-term follow-ups or explore the neural mechanisms of the differences between depressive and anxious rumination.ConclusionOur results contribute to the existing literature on the psychological mechanisms underlying aberrant cognition in depression. These findings could provide guidance for clinical practice and individualized precision treatment of cognitive biases in major depressive disorder. Therefore, rumination-focused therapies would be tailored differently for melancholic versus anxious subgroups.